2009
DOI: 10.1111/j.1872-034x.2009.00492.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of drug‐induced liver injury in the elderly

Abstract: Elderly patients with DILI show different clinical features than younger patients with DILI. These features should be taken into account in the diagnosis and treatment of DILI in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 10 publications
2
24
1
Order By: Relevance
“…37,38 A recent study in Japan directly evaluated the clinical characteristics of DILI in a predominantly elderly population consisting of 142 hospitalized patients. 39 They found that older patients (!75 years) had higher alkaline phosphatase levels, were taking a greater number of concomitant drugs at liver injury onset, and developed cholestatic liver injury more frequently. Indeed, an important consideration in the elderly is their use of multiple medications due to underlying illnesses, which may contribute to their increased risk of serious ADRs through alterations in cytochrome P450 expression and activity.…”
Section: Female Sexmentioning
confidence: 99%
See 1 more Smart Citation
“…37,38 A recent study in Japan directly evaluated the clinical characteristics of DILI in a predominantly elderly population consisting of 142 hospitalized patients. 39 They found that older patients (!75 years) had higher alkaline phosphatase levels, were taking a greater number of concomitant drugs at liver injury onset, and developed cholestatic liver injury more frequently. Indeed, an important consideration in the elderly is their use of multiple medications due to underlying illnesses, which may contribute to their increased risk of serious ADRs through alterations in cytochrome P450 expression and activity.…”
Section: Female Sexmentioning
confidence: 99%
“…In addition, several studies have shown strong association between older age and cholestatic or mixed patterns of DILI. 22,23,30,39,41 Children No population-based studies have systematically examined the epidemiology of DILI in children. Nonetheless, DILI is a significant clinical problem because it accounts for up to 20% of ALF cases requiring liver transplant surgery.…”
Section: Female Sexmentioning
confidence: 99%
“…In addition to any effect of age on physiologic reserves, the influence of age may be multifactorial as it relates to the number and type of medications and underlying comorbidities. In a recent Japanese study of 396 hospitalized patients with acute hepatitis (142 for DILI), age at least 65 was associated with a higher proportion of patients with DILI (62 vs. 26%, P < 0.001) [7]. Age at least 75 was associated with more frequent use of concomitant drugs and a cholestatic injury pattern.…”
Section: Risk Factorsmentioning
confidence: 99%
“…CYP3A is a prominent subfamily, and it has been postulated that age-related reductions in hepatic blood flow, and hepatic volume may have an impact on the clearance of some CYP3A substrates (Cotreau et al 2005). Yet, in practice, there is a lack of evidence that these alterations are significant or can be used to anticipate or manage DILI (Onji et al 2009;Stine et al 2013). Also, it has been pointed out that such changes would, if relevant to DILI, be expected to account for intrinsic rather than idiosyncratic DILI (Chalasani and Bjornsson 2010).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Indeed, it has been reported that older patients may be under-prescribed many medications, including statins (Barry et al 2007). Second, "polypharmacy," the presence of more than five medications in a routine regimen, has also been cited as a risk factor for DILI in the elderly (Bell and Chalasani 2009;Onji et al 2009;Stine et al 2013). Although it has been questioned as to whether polypharmacy itself a risk factor for DILI (Chalasani and Bjornsson 2010;Chalasani et al 2014), it is nevertheless a valid concern that with a longer list of medications, additional vigilance for the risk of hepatotoxicity is needed to ensure hepatic issues do not overtake other medical conditions as a primary focus.…”
Section: Introductionmentioning
confidence: 99%